Sarcopenia and its association with falls and fractures in older adults: A systematic review and meta‐analysis. Issue 3 (16th April 2019) - Yeung, Suey S.Y.; Reijnierse, Esmee M.; Pham, Vivien K.; Trappenburg, Marijke C.; Lim, Wen Kwang; Meskers, Carel G.M.; Maier, Andrea B.
Abstract: Sarcopenia is a potentially modifiable risk factor for falls and fractures in older adults, but the strength of the association between sarcopenia, falls, and fractures is unclear. This study aims to systematically assess the literature and perform a meta‐analysis of the association between sarcopenia with falls and fractures among older adults. A literature search was performed using MEDLINE, EMBASE, Cochrane, and CINAHL from inception to May 2018. Inclusion criteria were the following: published in English, mean/median age ≥ 65 years, sarcopenia diagnosis (based on definitions used by the original studies' authors), falls and/or fractures outcomes, and any study population. Pooled analyses were conducted of the associations of sarcopenia with falls and fractures, expressed in odds ratios (OR) and 95% confidence intervals (CIs). Subgroup analyses were performed by study design, population, sex, sarcopenia definition, continent, and study quality. Heterogeneity was assessed using the I 2 statistics. The search identified 2771 studies. Thirty‐six studies (52 838 individuals, 48.8% females, and mean age of the study populations ranging from 65.0 to 86.7 years) were included in the systematic review. Four studies reported on both falls and fractures. Ten out of 22 studies reported a significantly higher risk of falls in sarcopenic compared with non‐sarcopenic individuals; 11 out of 19 studies showed a significant positive association with fractures. Thirty‐three studies (45 926 individuals) were included in the meta‐analysis. Sarcopenic individuals had a significant higher risk of falls (cross‐sectional studies: OR 1.60; 95% CI 1.37–1.86, P < 0.001, I 2 = 34%; prospective studies: OR 1.89; 95% CI 1.33–2.68, P < 0.001, I 2 = 37%) and fractures (cross‐sectional studies: OR 1.84; 95% CI 1.30–2.62, P = 0.001, I 2 = 91%; prospective studies: OR 1.71; 95% CI 1.44–2.03, P = 0.011, I 2 = 0%) compared with non‐sarcopenic individuals. This was independent of study design, population, sex, sarcopenia definition, continent, and study quality. The positive association between sarcopenia with falls and fractures in older adults strengthens the need to invest in sarcopenia prevention and interventions to evaluate its effect on falls and fractures.